2016
DOI: 10.1108/tr-05-2015-0018
|View full text |Cite
|
Sign up to set email alerts
|

Toward extending creative tourism: participatory experience tourism

Abstract: Purpose While the “creative turn” in everyday life has led to rapid development of creative tourism, not all forms of creative tourism use the same intensity of creative involvement. It is possible to distinguish between more passive and active involvement. In parallel, a “social turn” has led to popularity of forms of tourism, such as volunteer tourism, involving active participation. The purpose of this paper is to put forward ideas and present eclectic observations on active tourist participation around bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 25 publications
0
32
0
2
Order By: Relevance
“…Based on the low density of some areas on the map, several issues appear to be underresearched or in an embryonic phase, namely the role of co-creation between organizations and tourists inside Cluster E (Ross et al, 2017; Zatori, 2016), the identification of a concrete way which creative tourism activities can improve urban tourism within Cluster C (Carvalho, Ferreira, & Figueira, 2016; Marques & Borba, 2017; Wattanacharoensil & Schuckert, 2016) and the new concept of the participatory tourism experience in Cluster B (de Bruin & Jelincic, 2016; Everingham, 2015). The results allow some opportunities for future research on creative tourism to be identified.…”
Section: Analysis and Resultsmentioning
confidence: 99%
“…Based on the low density of some areas on the map, several issues appear to be underresearched or in an embryonic phase, namely the role of co-creation between organizations and tourists inside Cluster E (Ross et al, 2017; Zatori, 2016), the identification of a concrete way which creative tourism activities can improve urban tourism within Cluster C (Carvalho, Ferreira, & Figueira, 2016; Marques & Borba, 2017; Wattanacharoensil & Schuckert, 2016) and the new concept of the participatory tourism experience in Cluster B (de Bruin & Jelincic, 2016; Everingham, 2015). The results allow some opportunities for future research on creative tourism to be identified.…”
Section: Analysis and Resultsmentioning
confidence: 99%
“…Other studies aim at explaining the development of new tourism trends all around the world. Such papers study fields like dark tourism (Farmaki, 2013), medical (Lam et al, 2011), creative (de Bruin & Jelinčić, 2016), wine (Quadri-Felitti & Fiore, 2016) and other types of tourism which have become more relevant during the past decades (De Micco et al, 2017). The common factor of all these fields is the relevance that new, creative, and experiential events may have in the value perception and consequent willingness to pay that visitors may have when selecting a location to visit.…”
Section: Literature Reviewmentioning
confidence: 99%
“…• Co-creation in creative tourism Bruin and Jelinčić (2016) focused on the active role of tourists in the creative tourist experience. They considered the way in which, although the "creative shift" in everyday life has led to the rapid growth of creative tourism, not all forms of creative tourism incorporate the same intensity of creative involvement.…”
Section: • Creative Tourist Experiencementioning
confidence: 99%